2023
DOI: 10.1002/adfm.202301256
|View full text |Cite
|
Sign up to set email alerts
|

Cascade‐Responsive “Oxidative Stress Amplifiers” Simultaneously Destroy Lysosomes and Co‐Deliver CRISPR/Cas9 to Enhance Oxidative Damage in Tumor

Abstract: Amplifying intracellular oxidative stress by organelle‐targeted reactive oxygen species (ROS) production combined with tumor cell‐specific gene disruption is a promising strategy for tumor treatment. However, due to the vulnerability of CRISPR/Cas9 ribonucleoproteins (RNPs) to ROS, co‐delivery of CRISPR/Cas9 RNPs and ROS generators to enhance the sensitivity of tumor cells to oxidative stress remains challenging. Herein, a cascade‐responsive “oxidative stress amplifier” (named DR‐TAF‐pHT/FA) is proposed, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…As displayed in Figure f, cells treated with GZABEF + L had the weakest red fluorescence compared with other treatments, confirming the lowest MMP and the most severe mitochondrial damage. High levels of ROS in cells may also disrupt the lysosomal membrane, which is essential for maintaining cell proliferation . As shown in Figure S7, the strongest green fluorescence was found in the GZABEF + L group, indicating the most serious lysosomal damage.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As displayed in Figure f, cells treated with GZABEF + L had the weakest red fluorescence compared with other treatments, confirming the lowest MMP and the most severe mitochondrial damage. High levels of ROS in cells may also disrupt the lysosomal membrane, which is essential for maintaining cell proliferation . As shown in Figure S7, the strongest green fluorescence was found in the GZABEF + L group, indicating the most serious lysosomal damage.…”
Section: Resultsmentioning
confidence: 98%
“…High levels of ROS in cells may also disrupt the lysosomal membrane, which is essential for maintaining cell proliferation. 23 As shown in Figure S7, the strongest green fluorescence was found in the GZABEF + L group, indicating the most serious lysosomal damage. These results demonstrated that GZABEF could disrupt intracellular redox homeostasis under laser irradiation through the production of a large number of alkyl radicals, the consumption of endogenous and exogenous GSH, and the inhibition of GPX4 activity, ultimately inducing mitochondriamediated cell apoptosis.…”
Section: Intracellular Gzabef-induced Oxidative Damagementioning
confidence: 85%
“…9 In contrast, CRISPR/Cas9 RNP complexes could be directly delivered into cells for rapid and highly efficient genome editing without transcription and translation. 10 The preformed RNP also reduces the possibility of off-target events and minimizes immunogenicity. 11 Nevertheless, the delivery of the RNP also faces many difficulties: RNP is easily denatured and has negligible intracellular delivery activity due to the high molecular weight of Cas9 (160 kDa) and sgRNA (∼31 kDa, ∼130 bases).…”
Section: Introductionmentioning
confidence: 99%